Effect of back support belt on musculoskeletal discomfort during simulated manual handling of loads among male agricultural workers - Tajul Ariffin, Muhammad Zulhaily; Ng, Yee Guan; Lim, Poh Ying; Adenan, Nur Syahirah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: The usage of back support belt for manual handling activities particularly lifting/lowering of loads in occupational setting has been a sore point of conflicting agreement between industrial practitioners and academician on its effectiveness in prevention of back injuries. As such, this pre-test and post-test experimental study was designed to investigate the effectiveness of back support belt in reducing localized musculoskeletal discomfort among male agricultural workers. Methods: A total of 38 subjects were randomly assigned into control and intervention groups (19 subjects in each group). The subjects were required to carry out a series of lifting and lowering of incremental weight load similar to the protocol as described in Progressive Isoinertial Lifting Evaluation (PILE) techniques. After completing each lift, subjects were required to rate the discomfort felt in the back region using the Localized Musculoskeletal Discomfort questionnaire. Results: Results showed that only several pairs showing statistically significant differences with no discernible trend. Within the control group, the median calculated from group data showed an overall increased discomfort rating as the weight load increases except for 19.4kg but an overall decreased discomfort within intervention group. Comparison between control and intervention group for post-test results showed significant difference between 5.9kg and middle back although the trend of LMD ratings across body part investigated may suggest interesting relationship. Conclusion: Despite positive subjective perception amongst the wearer as conveyed by industrial practitioners, the epidemiological data, clinical trials, and various other experimental studies in the past few decades including in this study has not shown sufficient evidence of effectiveness.